Peran teknologi dalam manajemen risiko dan inovasi perbankan syariah - Rahmadana, Muhammad Ilham Putra (Maliki Interdisciplinary Journal, 2025)
In the digital era marked by rapid advances in technology, Islamic banking faces significant challenges and opportunities in maintaining sustainability and competitiveness. This article analyzes the role of digital technology such as Big Data, Artificial Intelligence (AI), and Blockchain strengthening risk management and encouraging innovation in Islamic banking products and services. Through a qualitative approach with literature studies, this article highlights how the use of technology can increase operational efficiency, facilitate access to services, and help Islamic banking identify and manage risks more accurately. However, this digital transformation also faces various obstacles such as low digital literacy, limited human resources, and threats to cyber security. Therefore, synergy between technology, sharia governance and strong regulations is the key to creating an adaptive, innovative and sustainable sharia financial system in the digital era.